Investigation of the Cementation of Copper on Iron (The Australasian Institute of Mining and Metallurgy, 1972)
The kinetic and practical aspects of the extraction of copper from copper-rich solutions by cementation on iron was investigated. Tests were made on the effect of stirring speed, cupric sulphate concentration, acid concentration, temperature, and ferric sulphate concentration on the reaction rate and excess iron consumption.Most kinetic investigations were conducted under a nitrogen atmosphere to prevent any oxidation of the iron or copper metals. The stirring mechanism for all tests incorporated the use of a rotating impeller above a static disc in the solution. The activation energy for cementation on the steel disc at high stirring speed was 8·6 kcal/mole, indicating a predominant chemical control.Increasing the pH first decreased, then above pH 3, increased the reaction rate. Additions of sodium sulphate also significantly increased the reaction rate.The use of high temperature and high pH under an inert atmosphere has been suggested for increasing the reaction rate and producing a high purity sponge copper product.